L’allucinazione: dalla psicopatologia classica alla teoria della nascita - Migliorini, Vanina; Ramozzi, Clelia (Il sogno della farfalla, 2022)
Hallucination has been object of scientific debate for many decades. However, despite its clinical relevance, the scientific community has failed to reach a shared understanding of this phenomenon. The authors of this article analyse the main contributions on this topic drawing from psychoanalytic and phenomenological studies. Moreover, it is highlighted how the human birth theory elaborated by the psychiatrist Massimo Fagioli identifies in the alteration of the non-conscious mental reality the pathogenesis of hallucination. The authors therefore conclude that Fagioli’s theory may be crucial to offer new perspectives on many unsolved questions related to this phenomenon.